Learning Management in Developing Students' Hard Skills and Soft Skills - Omo Permana; Sutaryat Trisnamansyah; Hendi Suhendraya Muchtar; Kingking Muttaqien; Yoyo Sudaryo (Tarbawi, 2021)
This study aims to describe and analyze learning management in developing students' hard Skills and soft Skills at STIE INABA Bandung. This study uses a qualitative research method with a case study design. Data was collected by means of in-depth interviews, participant observation and documentation. After the data is obtained then it is organized, interpreted, analyzed and then concluded. While checking the validity of the data is done by triangulation of sources and methods. The results in this study are: 1) learning planning in developing students' hard Skills and soft Skills, carried out by compiling syllabus and semester learning plans (RPS), using various approaches, strategies, methods; 2) the implementation of learning in developing students' hard Skills and soft Skills is carried out using various methods, strategies, models and habituation of attitudes; 3) evaluation of learning in developing students' hard Skills and soft Skills, carried out by means of affective assessment and cognitive assessment; 4) learning outcomes in developing students' hard Skills and soft Skills, namely an increase in student abilities; 5) the problems faced in developing the hard Skills and soft Skills of students at STIE INABA Bandung include the competence of lecturers; student readiness, the use of one-way learning models, as well as the influence of different student environments; 6) Efforts made by STIE INABA tertiary institutions to overcome obstacles in instilling students' hard Skills and soft Skills include: preparing appropriate learning plans, using appropriate learning strategies, methods and models, providing models or examples by lecturers in attitude and speech, involving lecturers in seminars, workshops or training in order to develop appropriate learning management.